Inter-layer and inter-subject variability of diurnal gene expression in human skin. Issue 4 (31st December 2022) - del Olmo, Marta; Spörl, Florian; Korge, Sandra; Jürchott, Karsten; Felten, Matthias; Grudziecki, Astrid; de Zeeuw, Jan; Nowozin, Claudia; Reuter, Hendrik; Blatt, Thomas; Herzel, Hanspeter; Kunz, Dieter; et al.
Abstract: The skin is the largest human organ with a circadian clock that regulates its function. Although circadian rhythms in specific functions are known, rhythms in the proximal clock output, gene expression, in human skin have not been thoroughly explored. This work reports 24 h gene expression rhythms in two skin layers, epidermis and dermis, in a cohort of young, healthy adults, who maintained natural, regular sleep-wake schedules. 10% of the expressed genes showed such diurnal rhythms at the population level, of which only a third differed between the two layers. Amplitude and phases of diurnal gene expression varied more across subjects than layers, with amplitude being more variable than phases. Expression amplitudes in the epidermis were larger and more subject-variable, while they were smaller and more consistent in the dermis. Core clock gene expression was similar across layers at the population-level, but were heterogeneous in their variability across subjects. We also identified small sets of biomarkers for internal clock phase in each layer, which consisted of layer-specific non-core clock genes. This work provides a valuable resource to advance our understanding of human skin and presents a novel methodology to quantify sources of variability in human circadian rhythms.